La conciliación extrajudicial previo al procedimiento de divorcio, para establecer el régimen de tenencia o visitas y garantizar el principio de interés superior del niño, niña y adolescente - Astudillo Cobos, Baleria Abigail (2023)
General Organic Code of Processes, where the requirements for its termination are contemplated, as well as its causes, one of them: divorce. Regarding these legal figures, it has been throughout history, the cause of various conflicts, then arises the need to regulate these social relations through written regulations that are mandatory for the parties, in order to protect the common interest. and peace between people at the time of marital dissolution. Therefore, we must take into account the importance of the family, being the same, the basis of society, which is why, within a marital dissolution process, it is essential to guarantee the best interests of children and adolescents, being feasible to do it through extrajudicial conciliation, an institution that is constituted as an alternative mechanism for the solution of conflicts, where the parties go before a conciliation center, in which they will be attended by a neutral third party called a conciliator who will seek a consensual solution to the conflict. In the dissolution of the divorce having minor children, the conciliator will seek solutions in terms of alimony, tenure and visitation regime; Once the parties reach a consensual agreement regarding all the aforementioned aspects, it will be established in a document that will be issued by the conciliator, which will be attached to the divorce petition, this being a mandatory requirement for the authority competent authority admits the claim, that is, accepts and begins the divorce process presented by the parties.